2004
DOI: 10.1002/cpp.410
|View full text |Cite
|
Sign up to set email alerts
|

The factor structure of the Brief Symptom Inventory: intellectual disability evidence

Abstract: The use of psychometrics to assess the mental health of people with mild intellectual disabilities is a developing field of clinical and methodological interest. The available measures however tend to be few in number, with an even smaller minority progressing through the required rigorous psychometric development process. An assessment and potential outcome measure that has begun to be employed with people with intellectual disabilities is the Brief Symptom Inventory. This study examines the construct validit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 19 publications
3
44
0
Order By: Relevance
“…The authors conclude that the BSI could be utilized as an outcome measure to assess the effectiveness of clinical interventions in persons with intellectual disabilities. In 2004, the same authors [21] performed a factor analysis of the BSI with a sample of 355 individuals with mild cognitive delays and found that 8 clear and interpretable factors emerged. They concluded that people with DD respond to a large proportion of items on the BSI in a manner similar to the non-DD population.…”
Section: Diagnosismentioning
confidence: 96%
“…The authors conclude that the BSI could be utilized as an outcome measure to assess the effectiveness of clinical interventions in persons with intellectual disabilities. In 2004, the same authors [21] performed a factor analysis of the BSI with a sample of 355 individuals with mild cognitive delays and found that 8 clear and interpretable factors emerged. They concluded that people with DD respond to a large proportion of items on the BSI in a manner similar to the non-DD population.…”
Section: Diagnosismentioning
confidence: 96%
“…However, studies have shown inconsistent dimensional structures for the BSI with a varying number of dimensions (Hayes, 1997; Johnson et al, 1996; Kellett et al, 2004; Ruiperez et al, 2001). For example, Piersma and colleagues’ study (1994) with a sample size of 217 suggested that the BSI provides only a unidimensional measure of general psychological distress.…”
Section: Introductionmentioning
confidence: 99%
“…Kellet, Beail, Newman, and Hawes (2004) conducted a factor analytic study of the Brief Symptom Inventory (BSI). The BSI screens for symptoms related to somatization, interpersonal sensitivity, anxiety, depression, phobia, paranoid ideation, hostility, psychoticism and obsessive-compulsive disorders.…”
Section: Adaptations and Developments In Treatment Methodsmentioning
confidence: 99%